First Order Reactant in Magneto-Hydrodynamic Turbulence before the Final Period of Decay in Presence of Dust Particle (Bangladesh Journal of Scientific and Industrial Research, 2010)
Following Deissler's theory, the decay for the concentration fluctuation of a dilute contaminant undergoing a first order chemical reaction in MHD turbulence at times before the final period in presence of dust particle is studied and have considered correlations between fluctuating quantities at two and three point. Two and three point correlation equations are obtained and the set of equations is made to determinate by neglecting the quadruple correlations in comparison to the second and third order correlations. The correlation equations are converted to spectral form by taking their Fourier transforms. Finally we obtained the Decay law of magnetic energy for the concentration fluctuations before the final period in presence of dust particle by integrating the energy spectrum over all wave numbers. Keywords: MHD Turbulence; First order reactant; Dust particle; Decay before the final period DOI: 10.3329/bjsir.v45i1.5182 Bangladesh J. Sci. Ind. Res. 45(1), 39-46, 2010